Proceedings of the 2023 year-end workshop with the partners on Sustainable Intensification of Mixed Farming Systems (SI-MFS) - Haque, Abdul; Bhuiya, Shaheen; Ahmed, S.; Bhandari, Humnath (International Rice Research Institute, 2023)
The 2023 year-end workshop with the national partners from the CGIAR Initiative SIMFS was held on 2 December in Hotel Sarina, Dhaka, Bangladesh. The meeting was presided over by Dr. Humnath Bhandari, IRRI Representative for Bangladesh. Scientists from different NARSE organizations (BARI, BRRI, BLRI) were present in this workshop.